Шляхи формування джерельної бази тлумачної лексикографії сучасної української літературної мови - Гнатюк, І. (Лексикографічний бюлетень, 2015)
Scientific article contains determining the direction of leading Ukrainian modern lexicography to secure renewed source basis.